MATERI PEMBELAJARAN ESSEN UND TRINKEN DALAM GAME WILDSCHLANGE UNTUK KETERAMPILAN MEMBACA KELAS XI SEMESTER 2 - Lestari, Weny Puji; Pujosusanto, Ari (LATERNE, 2021)
German is one of the foreign language subjects in SMA, SMK, and MA in accordance with the 2013 curriculum. In German subjects, students must master language skills. Reading skills are the first skills that are possible for students to learn in German language learning. However, reading skills are still not mastered by students, especially in selectives licenses. Based on the low ability of students to select Lesen, especially on the Essen und Trinken theme, educators must apply learning techniques that are more attractive to students. Learning techniques that can attract students' interest are through games. Based on this, this study aims to describe the German language teaching materials for class XI semester 2 students that can be used in the Wildschlange game according to the 2013 curriculum. This research is a qualitative research with literature study method. The data sources used are from 3 German books, namely Deutsch ist einfach 2, Studio D A1, and Netzwerk A1 and from the internet, namely Goethe Institut Glasglow. The data used are in the form of Wortschatz and short text or dialogue text. Furthermore, data from all sources were analyzed based on the 2013 curriculum which included the suitability of the data with the theme Essen und Trinken, Basic Competence 3.3, indicators of competency achievement, and learning objectives. Based on the results of data analysis, 65 data were obtained in the form of Wortschatz and 8 data in the form of short texts or dialogue texts with the theme Essen und Trinken. After that, the data is processed according to the concept to be included in the Wildschlange game through the zonacacing application and how to use the game is arranged to make it easier for students to use it.